The rise of social theory - Heilbron, Johan (Minneapolis University of Minnesota Press, 1995)
The Rise of Social Theory offers a brilliant account of the origins of social theory and sociology, providing a vivid portrayal of intellectual culture between the Enlightenment and the age of Romanticism. It is a methodologically innovative work that combines social and intellectual history to examine changes in the social sciences, alone with the conditions under which these changes occurred